Co-existence of t(9;22) and t(8;21) in primary blast phase of chronic myelogenous leukemia: clinical experience and literature review - Zhang, Yuanfeng (Int J Clin Exp Pathol, 2019)
Rare chronic myelogenous leukemia (CML) patients manifested as the primary blast phase without a chronic and accelerated phase. The occurrence of a t(8;21) translocation in secondary blast phase of CML or Philadelphia chromosome positive acute myelogenous leukemia (Ph+ AML) has been reported previously. No case of primary blast phase of chronic myelogenous leukemia (CML-BP) bearing one clone with t(9;22) and t(8;21) simultaneously has been reported. One Chinese patient presenting with extensive spontaneous ecchymosis and enlarged spleen diagnosed as acute myelogenous leukemia (AML) by smear and immunophenotype was given chemotherapy including daunorubicin 3 days and cytarabine 7 days without a tyrosine kinase inhibitor (TKI) drug at the beginning. Fresh frozen plasma and 4-factor prothrombin complex concentrate was also transfused for coagulation disorder. However, fusion genes BCR/ABL p210 and AML1/ETO were both positive and karyotype analysis showed the abnormalities of t(9;22) and t(8;21) in the same clones. Bone marrow aspirate on 7th day of chemotherapy indicated hypocellularity with 45% blasts remaining. Cytarabine was prolonged to nine days combined with imatinib 600 mg per day. His bone marrow aspirate after complete remission revealed t(8;21) clones disappearing, especially FISH of bone marrow smear detecting the BCR/ABL fusion signals in the basophilic erythroblasts, which confirmed his diagnosis as primary blast phase of CML rather than Ph+ AML. Thus, we report for the first time one patient diagnosed as primary blast phase of CML presenting with t(9;22) and t(8;21) simultaneously.